2004
DOI: 10.2308/acch.2004.18.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on Recent Trends in Pro Forma Reporting

Abstract: This study provides descriptive evidence on the controversial trend adopted by many firms in recent years of reporting earnings figures on a pro forma basis. pro forma earnings exclude normal income statement items that managers deem to be nonrecurring or nonrepresentative of ongoing operations. We examine a large sample of actual pro forma press releases issued between January 1998 and December 2000. We find that pro forma announcers tend to be relatively “young” firms that are concentrated primarily in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2
20

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 9 publications
3
90
2
20
Order By: Relevance
“…Although evidence is found for the strategic use of alternative performance measures (e.g. Doyle and Soliman, 2002;Bhattacharya et al, 2004;Lougee and Marquardt, 2004;Bowen et al, 2005;Entwistle et al, 2005;Black and Christensen, 2009;Doyle et al, 2013), results suggest that reported alternative performance measures are relevant for investor decisionmaking (e.g. Bhattacharya et al, 2003;Brown and Sivakumar, 2003;Lougee and Marquardt, 2004) and provide incremental information beyond the net income number alone.…”
Section: Other Disaggregations Of Earningsmentioning
confidence: 83%
“…Although evidence is found for the strategic use of alternative performance measures (e.g. Doyle and Soliman, 2002;Bhattacharya et al, 2004;Lougee and Marquardt, 2004;Bowen et al, 2005;Entwistle et al, 2005;Black and Christensen, 2009;Doyle et al, 2013), results suggest that reported alternative performance measures are relevant for investor decisionmaking (e.g. Bhattacharya et al, 2003;Brown and Sivakumar, 2003;Lougee and Marquardt, 2004) and provide incremental information beyond the net income number alone.…”
Section: Other Disaggregations Of Earningsmentioning
confidence: 83%
“…8 Several studies argue that managers can use non-GAAP earnings opportunistically to increase equity valuations or garner private benefits. For example, Bhattacharya et al (2004) find that the use of non-GAAP earnings increases dramatically when the earnings and stock prices of the respective firms start to decline. Bowen et al (2005) look at the strategic emphasis managers place on non-GAAP earnings and find that managers tend to emphasize the metric that portrays better firm performance.…”
Section: Non-gaap Earnings and Board Independencementioning
confidence: 97%
“…First, prior research finds that non-GAAP earnings are used both (1) to inform equity investors (e.g., Bradshaw and Sloan 2002;Brown and Sivakumar 2003;Bhattacharya et al 2003;Lougee and Marquardt 2004) and (2) to opportunistically mislead them (e.g., Bradshaw and Sloan 2002;Doyle et al 2003;Bhattacharya et al 2003;Lougee and Marquardt 2004;Bhattacharya et al 2004;Bowen et al 2005;Black and Christensen 2009;Doyle and Soliman 2009;Brown et al 2010). Rather than attempting to distinguish between these alternatives, which need not be mutually exclusive, we provide evidence on cross-sectional variation in opportunism by examining how the nature of the exclusions (recurring versus transitory) and their use to meet the analyst forecast vary with board independence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sample extends Bhattacharya et al's (2007) sample and is similar to Brown et al's (2012) sample. We begin our hand collection in 1998 Q1 since manager‐adjusted pro forma earnings were not widely reported in the US prior to 1998 (see Bhattacharya et al, 2004, for a detailed analysis of time trends in pro forma reporting). Table 1 summarizes our sample selection procedures.…”
Section: Sample Selection Variable Measurement and Descriptive Ementioning
confidence: 99%